Iron Elbow and Straight-Chain Tool to Reduce Slip on Wood Transportation: An Experimental Study - Yuniawati Yuniawati; Mutia Herni Ningrum (Unit Research and Knowledge, School of Business and Management, Institut Teknologi Bandung, 2023)
Abstract. One of the obstacles in transporting wood is the occurrence of slippage. Slippage results in low productivity of timber transport with high production costs and soil damage. The research method is an experimental approach, namely designing, manufacturing and testing the supporting tools in the form of angle iron and straight iron chain. The research objective was to determine the effect of the use of assistive devices on slippage, productivity, wood transport costs and soil damage. The results showed that: 1). Tools from the wheelbarrows of the conveyance wheel from the straight iron chain of the slope class 0-8%, 9-15%, and 16-25% can minimize the occurrence of slippage higher than not using this tool, increase the wood transportation productivity, low transportation production costs, and minimize soil damage; 2). Elbow iron and straight-chain tools are the most efficient and effective. 3). The use of tools in the transportation of wood in slopes 0-8%, 9-15%, and 16-25% is recommended for smooth production. Keywords: Iron elbow, straight chain, productivity, production cost, soil damage Abstrak. Salah satu hambatan dalam pengangkutan kayu adalah terjadinya selip. Selip berakibat pada rendahnya produktivitas pengangkutan kayu dengan biaya produksi yang tinggi dan terjadinya kerusakan tanah. Metode penelitian adalah pendekatan eksperimen yaitu merancang, membuat dan uji coba alat bantu berupa besi siku dan rantai besi lurus. Tujuan penelitian adalah untuk mengetahui pengaruh penggunaan alat bantu terhadap selip, produktivitas, biaya pengangkutan kayu dan kerusakan tanah. Hasil penelitian menunjukkan bahwa : 1). Alat bantu dari sarung roda alat angkutan dari rantai besi lurus kelas kelerengan 0-8%, 9-15% dan 16-25% dapat meminimalkan terjadinya selip lebih tinggi daripada tidak menggunakan alat bantu, meningkatkan produktivitas pengangkutan kayu, biaya produksi pengangkutan rendah, dan meminimalkan kerusakan tanah; 2). Alat bantu dari besi siku dan rantai besi lurus paling efisien dan efektif; 3). Penggunaan alat bantu pada kegiatan pengangkutan kayu di kelerengan 0-8%, 9-15% dan 16-25% dianjurkan untuk kelancaran produksi. Kata kunci: Besi siku, rantai lurus, produktivitas, biaya produksi, kerusakan tanah